2015
DOI: 10.1016/j.jvs.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Varicosity avUlsion Later or Synchronized (AVULS): A Randomized Clinical Trial

Abstract: Mini AbstractA randomised clinical trial comparing simultaneous endovenous ablation and phlebectomy with endovenous ablation and delayed phlebectomy successfully recruited and treated 101 patients. Combined endovenous ablation and phlebectomy delivers improved clinical outcomes and a reduced rate of need for further procedures, in addition to early Quality of Life improvements. MethodsPatients undergoing local anaesthetic endovenous thermal ablation were randomised to either simultaneous phlebectomy or delaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 4 publications
3
24
1
Order By: Relevance
“…If required (if symptomatic visible varicosities) and with patient consent, concomitant phlebectomies were then performed using standard Oesch hook technique with local tumescent anaesthesia. 12,13 All patients received a single prophylactic dose of low molecular weight heparin at the completion of the procedure. Use of prophylactic antibiotics was left to the discretion of the treating surgeon.…”
Section: Interventionsmentioning
confidence: 99%
“…If required (if symptomatic visible varicosities) and with patient consent, concomitant phlebectomies were then performed using standard Oesch hook technique with local tumescent anaesthesia. 12,13 All patients received a single prophylactic dose of low molecular weight heparin at the completion of the procedure. Use of prophylactic antibiotics was left to the discretion of the treating surgeon.…”
Section: Interventionsmentioning
confidence: 99%
“…This study demonstrated a clinically and statistically significant 4-point reduction in VCSS score in the group receiving 60 minutes of treatment a day, suggesting an improvement in clinical severity of CVD following treatment with NMES, in line with that seen in randomised clinical trials after surgical intervention. [44][45][46] There was also a significant 6.29 point improvement in the disease specific AVVQ score in group C, which is above the accepted minimum important difference of 5 points in AVVQ. The control group demonstrated a non-significant worsening of their AVVQ score.…”
Section: Discussionmentioning
confidence: 68%
“…A previous study reported that combined EVLA plus phlebectomy improved clinical outcomes and reduced the need for further procedures. 3 On the other hand, several investigators have also claimed that concomitant phlebectomy could be omitted because EVLA improved the symptoms. 4 Because of the use of conventional hooks, only superficial varicose veins near the incision site could be avulsed.…”
Section: Discussionmentioning
confidence: 99%